A Literature Review on Software Testing Techniques for Smartphone Applications - Khan, M. N. A.; Mirza, A. M.; Wagan, R. A.; Shahid, M.; Saleem, I. (Engineering, Technology & Applied Science Research, 2020)
Smartphone applications are getting popular and have become a necessity. There numerous smartphone applications ranging from entertaining to gaming and from utility to mission-critical. Almost everything on the web is now in hands of Smartphone users, which makes this domain very important and its quality should not be compromised. Achieving the desired quality is not an easy task for the mobile platform as it has its limitations. To produce a quality app, developers and testers need to test and assess the app in numerous ways to ensure the best trait of the application. In this concern, some efficient and mature techniques are required to test smartphone applications. In this study, the techniques, approaches, and models to assess mobile apps covering major prospects and angels to test mobile apps are identified. Our focus is on assessing the existing techniques and to evaluate them on standard validation parameters.